2006
DOI: 10.1097/01.tp.0000188620.72969.56
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation Reverses Functional Deficiencies in Circulating Dendritic Cell Subsets in Chronic Renal Failure Patients

Abstract: Deficiencies in the incidence and function of precursor DC can be reversed with successful renal transplantation achieving normal renal function. However, the finding of reduced incidence of circulating prePDC in the peripheral blood in RT recipients may be of significance in the pathogenesis of infections and malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…This hypothesis was recently supported in patients undergoing renal transplantation, where the afore existing deficiencies in incidence and function of precursor DC were reversed [27]. Moreover, serum from uremic patients, when added to culture medium, impaired DC-function in vitro, especially endocytosis and maturation [28].…”
Section: Discussionmentioning
confidence: 78%
“…This hypothesis was recently supported in patients undergoing renal transplantation, where the afore existing deficiencies in incidence and function of precursor DC were reversed [27]. Moreover, serum from uremic patients, when added to culture medium, impaired DC-function in vitro, especially endocytosis and maturation [28].…”
Section: Discussionmentioning
confidence: 78%
“…We and others have previously shown that circulating precursor PDCs are reduced in renal and cardiac transplant recipients. 18,22,23 PDCs isolated from recipients of renal transplants were functionally normal in response to viral stimulation, suggesting that the defect in antiviral response in renal transplant recipients was a reflection of the reduction in circulating precursor PDCs rather than an intrinsic abnormality of PDCs. Thus, the present studies were performed to address the consequence of reduced PDCs in the pathogenesis of EBV-related diseases using a NOD-SCID mouse lymphoma model.…”
Section: Discussionmentioning
confidence: 96%
“…Flow cytometric analysis of PDC-depleted PBMC fraction stained with anti-human CD123 ϩ mAbs confirmed approximately 50% reduction in the proportion of PDCs of total PBMCs approximately corresponding to the reduced proportion of PDCs in the peripheral blood of renal transplant recipients. 18 PDC-enriched PBMC mice received a further 1 ϫ 10 5 autologous PDCs from the same blood donor (positively isolated using Automacs) injected into each mouse in addition to PBMCs. The depletion and enrichment of PDCs were performed using BDCA-4 ϩ isolation kit and cells separated by Automacs as described.…”
Section: Humanized Nod-scid Mouse Model Of Ebv Infection and Lpdmentioning
confidence: 99%
See 2 more Smart Citations